Reabsorção radicular inflamatória externa em dentes decíduos com traumatismos dentários e fatores associados - Fernanda Carneiro de Moraes (2023)
Inflammatory external root resorption has been increasingly observed by pediatric dentists as a consequence of dental trauma in the primary dentition. The prognosis of this condition in the primary dentition is unfavorable, with rapid progression and, when not diagnosed and treated, can harm the development of the germ of the permanent successor tooth and lead to premature loss of the primary tooth. This study aims to identify the frequency and factors associated with inflammatory external root resorption in traumatized primary teeth. This is a retrospective cross-sectional study that clinically and radiographically evaluated primary incisors from the medical records of children treated and monitored for at least one year between 2007 and 2022 at a reference clinic for trauma to primary teeth in Belo Horizonte at the Faculty of Dentistry of the Federal University of Minas Gerais (FAO UFMG). Data collection from clinical records was carried out by two trained researchers and analysis of radiographs was carried out by a researcher trained and calibrated to identify inflammatory external root resorption. Two professors experienced in dental trauma and a radiology specialist were responsible for training and calibration (kappa = 0.7). The dependent variable was the presence of inflammatory external root resorption after dental trauma. The independent variables collected through clinical records were the child's sex and age, mother's education, non-nutritive sucking habit, oral hygiene, mobility, repeated trauma, immediate care and the type of dental trauma. In total, 508 teeth were analyzed using data from clinical records and radiographic examinations of 278 children aged between 6 and 72 months. Statistical analysis was performed using the Statistical Package for Social Science (SPSS) 25.0 software and included descriptive analysis, chi-square test and Poisson Regression with robust variance. Of the teeth evaluated, 20.9% (n= 106) showed inflammatory external root resorption. They were associated with inflammatory external resorption, seeking care 2 hours or more after dental trauma (RP= 1.49; CI=1.03-2.07; p=0.033), the presence of tooth mobility (RP= 2 .18; CI=1.49-3.21; p>0.001) and complicated fracture (PR=1.87; CI=1.10-3.16; p=0.019). It is concluded that the frequency of inflammatory external root resorption in traumatized primary teeth was moderate/high and was associated with late care, complicated fractures and tooth mobility.